Falla hepática aguda sobre crónica (ACLF), síndrome subdiagnosticado con alta mortalidad - García N, Daniela; Poniachik T, Jaime (Revista Hospital Clínico Universidad de Chile, 2021)
Acute on chronic liver failure is an increasingly recognized syndrome characterized by acute decompensation of chronic liver disease associated with organ failure and high short-term mortality. ACLF is frequent, affecting between 24 and 40% of patients admitted for complications of cirrhosis. Sepsis, active alcoholism, and relapse of chronic viral hepatitis are the most frequent precipitating factors. However, in up to 40%–50% of the cases of ACLF have no identifiable trigger. The stage of severity of Acute on chronic liver failure is very important because it allows us to stratify patients according to their prognosis, evaluate therapeutic response, determine transplant urgency, deciding intensive care unit admission, and also have a basis on which to decide therapeutic futility.